Natural and anthropogenic forcing during the last two centuries in the Ombrone delta (southern Tuscany - central Italy) - Tarragoni, Claudia; Bellotti, Piero; Davoli, Lina (Italian journal of engineering geology and environment, 2015)
This study describes advances in understanding of the recent evolution of the Ombrone River delta. Several aspects have been studied and updated: the stages of progradation and retreat of the shoreline from the Middle Ages, with particular reference to the last 200 years, have been reconstructed and the natural and/or human forcing responsible for the area’s evolution have been hypothesized. The processes that led to the formation and evolution of some small coastal lakes and the more recent evolution of the shoreline are defi ned. Monitoring of shoreline variations in the Ombrone Delta apex has been achieved by comparing aerial photos acquired in 1995, 1998, 2004, 2006 and 2010. The progressive landward migration of the shoreline has resulted in a realignment of the coast. Comparison with older erosion and progradation rates shows decreasing erosion rates along the delta apex with time: the erosion rate of the northern wing has reached peaks of around 14 m/yr (2004-2006), and then fallen to 4.5 m/yr in the latest period (2006-2010). The Ombrone River delta is characterized by the presence of beach ridges, ponds and, in the past, of a coastal lake. Morpho-bathymetric analysis and comparison with historical maps shows that during the XIX century, the historical lake preserved its geometry; only in the 1883 map seaward side presents an irregular geometry, while in the 1929 map the ponds have been represented for the fi rst time and are located seaward with respect to the XIX century beach ridge. Comparing morpho-bathymetric data of Chiaro Grande pond and submerged apical mouth, this study confi rmed the hypothesis about Chiaro Grande pond genesis in which its formation is based on the closure of a narrow sea stretch consequent to the emergence of a bar. The independence between the genesis of ponds and lake evolution, highlighting the importance of mouth bar growth as a recurrent mechanism for confi ning narrow sea stretches. The orientation of morphological features and the prevailing wave climate suggest a sediment transport from south to north.